The removal of carbon/nitrogen in continuous reactor - A. Hamid, Hazren; Muhamad, Mimi Suliza; Hamidon, Nuramidah; Harun, Hasnida; Mohamed Sunar, Norshuhaila; Ali, Roslinda (Penerbit UTHM, 2020)
The secondary wastewater treatment is process after primary wastewater treatment which is this process can more removal the suspended solid in wastewater. This treatment involves the biological process to remove the suspended solid in wastewater, which is consume the organic impurities as food, converting them into carbon dioxide, water, and energy for their own growth and reproduction. The secondary treatment objectives are to reducing the biochemical oxygen demand (BOD) and the effluent's suspended solids to appropriate levels. But in some case of wastewater need an advance treatment to reduce the level of contaminant especially nitrogen and carbon.